Pengaruh Lingkungan Kerja terhadap Motivasi Pegawai Polisi Kehutanan pada Dinas Lingkungan Hidup dan Kehutanan di Wilayah UPT Kesatuan Pengelolaan Hutan Jeneberang di Kabupaten Gowa - Uhud Darmawan Natsir; Dayani Isfahani Idris; Tenri S.P. Dipoatmodjo; Anwar Ramli; Rezky Amalia Hamka (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research targets to determine: The affect of the bodily work environment and non-bodily work surroundings on paintings motivation. The data in this have a look at have been received From statistics From Forestry Police employees on the Environmental And Forestry carrier in the UPT place Of The Jeneberang woodland management Unit In Gowa district who were inclined to be respondents. This research uses a quantitative form of studies. The facts supply Used Is primary facts acquired thru dispensing Questionnaires at the Environmental And Forestry carrier within the UPT region Of The Jeneberang forest management Unit In Gowa District. using the Roscoe sampling approach with a pattern of 60 forestry police personnel. The facts analysis technique uses a couple of linear regression the usage of the SPSS 22 software. The outcomes of this research imply that the bodily work surroundings and non-physical paintings surroundings together have a advantageous have an impact on on paintings motivation. which means that that the higher the working surroundings is felt, the more paintings motivation of forestry police employees will boom.